Barium titanate-based ceramic and preparation method thereof, and energy storage device
Patent Information
- Application Number
- CN202611147886.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
然而,电介质通常伴有温度依赖的相变和热诱导的能量损耗使得介电响应的不稳定和显著增加的能量损耗,从而导致高能量密度和温度稳定性难以同时兼得
[0014]本申请的第三方面提出了一种储能器件。根据本申请的实施例,包括第一方面所述的钛酸钡基陶瓷或采用第二方面所述的钛酸钡基陶瓷的制备方法制得的钛酸钡基陶瓷。由此,该储能器件具有前述钛酸钡基陶瓷的全部特征及优点,在此不再赘述。
Smart Images

Figure CN123003276A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of barium titanate-based ceramic materials, specifically relating to a barium titanate-based ceramic and its preparation method, as well as an energy storage device. Background Technology
[0002] With the widespread application of renewable energy, energy storage technology has become one of the key technologies. Traditional electrochemical energy storage suffers from suppressed charge migration at low temperatures and electrolyte decomposition at high temperatures, typically limiting its use to a limited temperature range of -40℃ to 60℃. Dielectric capacitors, as core components of high-power electronic systems, possess advantages such as ultrafast charge and discharge rates and superior power density. Furthermore, based on the energy storage mechanism of electric field-induced local dipole polarization, they have broader potential for energy storage applications in extreme environments, such as deep space exploration at temperatures as low as -90℃ and aerospace electronics and oil well exploration at temperatures as high as 300℃. High energy density in extreme environments requires the dielectric material, a key material for dielectric capacitors, to simultaneously satisfy high and stable polarization / dielectric response and low dielectric loss over a wide temperature range. However, dielectrics are often accompanied by temperature-dependent phase transitions and thermally induced energy losses, leading to unstable dielectric responses and significantly increased energy losses, making it difficult to simultaneously achieve high energy density and temperature stability. Therefore, improving the stability of the dielectric response of dielectrics over a wide temperature range, thereby achieving both high energy storage performance and temperature insensitivity over a wide temperature range, remains a significant challenge for dielectrics. Summary of the Invention
[0003] This application aims to at least partially address one of the technical problems in the related art. Therefore, the purpose of this application is to provide a barium titanate-based ceramic, its preparation method, and an energy storage device.
[0004] The first aspect of this application discloses a barium titanate-based ceramic. According to embodiments of this application, the chemical formula of the barium titanate-based ceramic is as follows: 0.48(Ba 0.76 Ca 0.2 Sr 0.04 TiO3)-(0.52-x)Bi(Mg 0.5 Ti 0.5 )O3-x(0.88NaNbO3-0.12CaTiO3); where, 0 <x<0.2。
[0005] The barium titanate-based ceramics described in the above embodiments of this application. Based on existing barium titanate-based ceramics, this application introduces a suitable proportion of Bi(Mg)... 0.5 Ti 0.5The synergistic effect of 0.88NaNbO3-0.12CaTiO3 and barium titanate-based ceramics enables them to maintain excellent dielectric energy storage performance and high-temperature stability in a wide temperature range of -70℃ to 300℃, thus overcoming the shortcomings of existing technologies.
[0006] In addition, the barium titanate-based ceramics according to the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, the value of x is 0.1-0.18.
[0007] In some embodiments of this application, the relative permittivity of the barium titanate-based ceramic is ≥600 within the temperature range of -70℃ to 300℃.
[0008] In some embodiments of this application, the total capacitance deviation of the barium titanate-based ceramic is <10% within the range of -70℃ to 300℃.
[0009] The second aspect of this application discloses a method for preparing the barium titanate-based ceramic described in the first aspect. According to embodiments of this application, the method includes the following steps: Includes the following steps: Weigh each metal source according to the stoichiometric ratio shown in the chemical formula of barium titanate-based ceramic, add grinding aid and perform first ball milling to obtain the first mixture; The first mixture is dried and then subjected to a first sintering to obtain a second mixture; Add a sintering aid and a grinding aid to the second mixture and perform a second ball milling to obtain a third mixture; After the third mixture is dried, a binder is added, and the mixture is pressed and sintered in the second stage to obtain a green embryo. The green embryo is subjected to a third sintering process to obtain the barium titanate-based ceramic. Thus, this application obtains a barium titanate-based ceramic exhibiting excellent dielectric energy storage performance and high-temperature stability over a wide temperature range of -70℃ to 300℃ by ball milling and sintering the metal precursor. Furthermore, this preparation method is simple to operate, requires no additional specific equipment, and is suitable for industrial production.
[0010] In addition, the method for preparing barium titanate-based ceramics according to the first aspect of the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, the metal source includes metal oxides and metal carbonates, and the grinding aid includes ethanol.
[0011] In some embodiments of this application, the working conditions parameters of the first sintering include: a temperature of 800℃-900℃ and a time of 2.5h-4h.
[0012] In some embodiments of this application, the working conditions parameters for the second sintering include: a temperature of 550℃-650℃ and a time of 2.5h-4h; The binder includes polyvinyl alcohol, the sintering aid includes MnO2, and the working conditions for the compression molding include: pressure of 150MPa-250MPa and time of 5min-15min.
[0013] In some embodiments of this application, the working conditions for the second sintering include: a temperature of 1050℃-1200℃ and a time of 1.5h-4h.
[0014] A third aspect of this application discloses an energy storage device. According to embodiments of this application, it includes barium titanate-based ceramic as described in the first aspect or barium titanate-based ceramic prepared using the preparation method described in the second aspect. Therefore, this energy storage device possesses all the features and advantages of the aforementioned barium titanate-based ceramic, which will not be elaborated further here.
[0015] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0016] Figure 1 The images show the X-ray diffraction analysis results of the barium titanate-based ceramics obtained in Examples 1, 2 and Comparative Example 1 of this application.
[0017] Figure 2 The graph shows the temperature dependence test results of the dielectric constant of the barium titanate-based ceramics obtained in Examples 1, 2 and Comparative Example 1 of this application.
[0018] Figure 3 This is a graph showing the PE variation test results of the barium titanate-based ceramic obtained in Comparative Example 1 of this application over a wide temperature range.
[0019] Figure 4 This is a graph showing the PE variation test results of the barium titanate-based ceramic obtained in Example 2 of this application over a wide temperature range.
[0020] Figure 5 This is a graph showing the PE variation test results of the barium titanate-based ceramic obtained in Example 1 of this application over a wide temperature range. Detailed Implementation
[0021] The embodiments of this application are described in detail below by way of example, and are intended to explain this application, but should not be construed as limiting this application.
[0022] The first aspect of this application discloses a barium titanate-based ceramic. According to embodiments of this application, the chemical formula of the barium titanate-based ceramic is as follows: 0.48(Ba 0.76 Ca 0.2 Sr 0.04 TiO3)-(0.52-x)Bi(Mg 0.5 Ti 0.5 )O3-x(0.88NaNbO3-0.12CaTiO3); where 0<x<0.2, for example, it can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.5, 1.8, 1.9 or a range between any of the aforementioned values, etc.
[0023] The barium titanate-based ceramic according to the above embodiments of the present application. On the basis of existing barium titanate-based ceramics, the present application simultaneously introduces Bi(Mg with an appropriate ratio 0.5 Ti 0.5 )O3 and 0.88NaNbO3-0.12CaTiO3, the two act synergistically to achieve that the barium titanate-based ceramic maintains excellent dielectric energy storage performance and high temperature stability in a wide temperature range of -70°C to 300°C, which makes up for the deficiencies in the prior art.
[0024] In addition, the barium titanate-based ceramic according to the above embodiments of the present application may also have the following additional technical features: In some embodiments of the present application, the value of x is 0.1-0.18, for example, it can be 0.1, 0.11, 0.15, 0.18 or a range between any of the aforementioned values, etc. Accordingly, by optimizing the value of x to regulate Bi(Mg 0.5 Ti 0.5 )O3 and 0.88NaNbO3-0.12CaTiO3, the dosage ratio of the two is further synergistically improved to enhance the dielectric energy storage performance and high temperature stability of the barium titanate-based ceramic.
[0025] In some embodiments of the present application, within the range of -70°C to 300°C, the relative dielectric constant of the barium titanate-based ceramic is ≥600, for example, it can be 600, 620, 650, 680, 700 or a range between any of the aforementioned values, etc. Accordingly, the barium titanate-based ceramic provided by the present application has excellent dielectric energy storage performance in a wide temperature range of -70°C to 300°C.
[0026] In some embodiments of the present application, within the range of -70°C to 300°C, the total capacitance deviation of the barium titanate-based ceramic is <10%, for example, it can be 1%, 3%, 5%, 8%, 9% or a range between any of the aforementioned values, etc. Accordingly, the barium titanate-based ceramic provided by the present application has excellent high temperature stability in a wide temperature range of -70°C to 300°C.
[0027] The second aspect of this application discloses a method for preparing the barium titanate-based ceramic described in the first aspect. According to embodiments of this application, the method includes the following steps: Includes the following steps: Weigh each metal source according to the stoichiometric ratio shown in the chemical formula of barium titanate-based ceramic, add grinding aid and perform first ball milling to obtain the first mixture; The first mixture is dried and then subjected to a first sintering to obtain a second mixture; Add a sintering aid and a grinding aid to the second mixture and perform a second ball milling to obtain a third mixture; After the third mixture is dried, a binder is added, and the mixture is pressed and sintered in the second stage to obtain a green embryo. The green embryo is subjected to a third sintering process to obtain the barium titanate-based ceramic. Thus, this application obtains a barium titanate-based ceramic exhibiting excellent dielectric energy storage performance and high-temperature stability over a wide temperature range of -70℃ to 300℃ by ball milling and sintering the metal precursor. Furthermore, this preparation method is simple to operate, requires no additional specific equipment, and is suitable for industrial production.
[0028] In addition, the method for preparing barium titanate-based ceramics according to the first aspect of the above embodiments of this application may also have the following additional technical features: In some embodiments of this application, the metal source includes metal oxides and metal carbonates, such as Bi2O3, BaCO3, CaCO3, MgO, TiO2, Na2CO3, SrCO3, Nb2O5, etc.; the grinding aid includes ethanol.
[0029] As an example, when x=0.18, Bi2O3 (4.9117g), BaCO3 (4.1681g), CaCO3 (0.6206g), MgO (0.4248g), TiO2 (3.3243g), Na2CO3 (0.5258g), SrCO3 (0.5495g), and Nb2O5 (1.3197g) can be mixed. Then, twice the mass of the total oxide powder can be added as an ethanol grinding aid. The mixture is then ball-milled at 260 rpm for 12 hours to obtain the first mixture.
[0030] In some embodiments of this application, the working conditions for the first sintering include: a temperature of 800℃-900℃, such as 800℃, 820℃, 850℃, 900℃, or any range between the aforementioned values; and a time of 2.5h-4h, such as 2.5h, 3.0h, 3.5h, 4h, or any range between the aforementioned values. This application uses the aforementioned working conditions for the first sintering process to pre-calcine the first mixture, which facilitates sufficient reaction between the raw materials to obtain a pure perovskite phase.
[0031] As an example, drying the mixture after ball milling may include the following process: heating on a hot table at 100℃-120℃ for 3-4 hours to achieve drying.
[0032] In some embodiments of this application, the working conditions parameters for the second sintering include: a temperature of 550℃-650℃, for example, 550℃, 580℃, 600℃, 650℃ or any of the aforementioned values; a time of 2.5h-4h, for example, 2.5h, 3.0h, 3.5h, 4h or any of the aforementioned values; the binder includes polyvinyl alcohol, the sintering aid includes MnO2, and the working conditions parameters for the compression molding include: a pressure of 150MPa-250MPa, for example, 150MPa, 180MPa, 200MPa or any of the aforementioned values; and a time of 5min-15min, for example, 5min, 8min, 10min or any of the aforementioned values. In this application, a binder such as polyvinyl alcohol (PVA) is introduced (the amount added can be 4%-7% of the mass of the third mixture, such as 5%) for granulation and tableting. The tablets are then sintered in a second process to remove the binder, which facilitates the subsequent sintering of the green sample after glue removal.
[0033] In some embodiments of this application, the working conditions for the second sintering include: a temperature of 1050℃-1200℃, such as 1050℃, 1100℃, 1150℃, 1200℃, or any range thereof; and a time of 1.5h-4h, such as 1.5h, 2.0h, 2.5h, 3h, or any range thereof. This application uses a third sintering process under the aforementioned working conditions to pre-fire the first mixture, which is beneficial for the further growth of perovskite ceramic grains and improves its crystallinity and density.
[0034] A third aspect of this application discloses an energy storage device. According to embodiments of this application, it includes barium titanate-based ceramic as described in the first aspect or barium titanate-based ceramic prepared using the preparation method described in the second aspect. Therefore, this energy storage device possesses all the features and advantages of the aforementioned barium titanate-based ceramic, which will not be elaborated further here.
[0035] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0036] Example 1 This embodiment provides a barium titanate-based ceramic with the following chemical formula: 0.48(Ba 0.76 Ca 0.2 Sr 0.04 TiO3)-(0.52-x)Bi(Mg 0.5 Ti 0.5 O3-x(0.88NaNbO3-0.12CaTiO3); where x=0.18, its preparation method includes the following steps: Bi₂O₃ (4.9117 g), BaCO₃ (4.1681 g), CaCO₃ (0.6206 g), MgO (0.4248 g), TiO₂ (3.3243 g), Na₂CO₃ (0.5258 g), SrCO₃ (0.5495 g), and Nb₂O₅ (1.3197 g) were mixed with twice the mass of the total oxide powder in ethanol and ball-milled at 260 rpm for 12 h. The slurry was then poured into a petri dish and dried by heating on a hot plate at 100 °C for 3 h. The dried powder was then pre-calcined in a muffle furnace at 850 °C at a heating rate of 5 °C / min for 3 h, and then cooled with the furnace. Next, the pre-fired powder was poured back into a ball mill jar for a second ball milling. Before ball milling, 0.5% MnO2 (by weight of the pre-fired powder) was added as a sintering aid, along with twice the weight of ethanol (by weight of the pre-fired powder). The milling continued at 260 rpm for 18 hours. The slurry was then poured out and dried on a hot plate at 100°C for 3 hours. The dried powder was then granulated and pressed into tablets with 5% PVA as a binder at a pressure of 200 MPa for 10 minutes. The pressed tablets were then heated to 600°C at a rate of 1.5°C / min for 3 hours to remove the added PVA binder, and allowed to cool naturally to room temperature. The debonded green sample was then heated to 1100°C at a rate of 5°C / min for 2 hours, and allowed to cool naturally to obtain a barium titanate-based dielectric energy storage ceramic with a wide temperature range stability.
[0037] Example 2 This embodiment provides a barium titanate-based ceramic and its preparation method, which differs from Example 1 mainly in that: (1) Barium titanate-based ceramics with x=0.1 in chemical formula were prepared by referring to the preparation method in Example 1.
[0038] Comparative Example 1 The main difference between this comparative example and Example 1 is: (1) Barium titanate-based ceramics with x=0 in chemical formula were prepared by referring to the preparation method in Example 1.
[0039] Test case This example tests the barium titanate-based ceramics obtained in the above embodiments and comparative examples.
[0040] Energy storage performance and high-temperature performance testing: The prepared ceramic sample was thinned and polished to approximately 50 micrometers. Then, a full-surface gold electrode was sputtered onto one side, and a 1 mm diameter gold electrode was sputtered onto the other side using a mask. The sample was then immersed in silicone oil and connected to a circuit. Its PE curve was measured using a ferroelectric analyzer. The PE curve test is considered a relatively intuitive characteristic test for distinguishing ferroelectrics, relaxors, and paraelectrics. Simultaneously, the change trend of the polarization intensity P under the action of an external electric field E can reflect domain inversion and energy conversion within the material. The PE curve in this test was measured using a radiant technologies Inc. ferroelectric analyzer, and the results were based on the following formula:
[0041]
[0042] The energy storage density U was calculated. e (Unit: J / cm) 3 and energy storage efficiency (unit%).
[0043] The wide-temperature energy storage density is obtained based on the variable-temperature PE test curve under an isoelectric field. During the variable-temperature test, the silicone oil is heated to the specified temperature using a variable-temperature stage and kept at that temperature for more than 30 minutes before the test begins.
[0044] The test results are shown in Table 1.
[0045] Table 1
[0046] Table 2
[0047] As shown in Tables 1 and 2, compared to Comparative Example 1, within a wide temperature range of -70 to 300°C, with -60°C, 25°C, and 200°C representing low-temperature, medium-temperature, and high-temperature operating conditions respectively, the energy storage density, energy storage efficiency, and relative permittivity of the embodiments in this application maintain good stability, and the total capacitance change rate is controlled within 10%. This indicates that the material has excellent energy storage temperature stability and dielectric response consistency within the range of -70 to 300°C. Furthermore, the X-ray diffraction analysis results of the barium titanate-based ceramics obtained in Examples 1, 2, and Comparative Example 1 are as follows: Figure 1 As shown. The temperature dependence test results of the dielectric constant of the barium titanate-based ceramics obtained in Examples 1, 2, and Comparative Example 1 are as follows. Figure 2 As shown. The wide-temperature-range PE variation test results of Comparative Example 1, Example 2, Example 1, and the obtained barium titanate-based ceramics are respectively shown in the figures. Figure 3 , Figure 4 and Figure 5 As shown, the temperature dependence of the dielectric constant decreases significantly with increasing x in the ultra-wide temperature range of -70℃ to 300℃, the temperature stability of the PE hysteresis loop is significantly improved, and the temperature stability of the energy storage performance is improved. This application yields a barium titanate-based ceramic that exhibits both excellent dielectric energy storage performance and high-temperature stability in the wide temperature range of -70℃ to 300℃.
[0048] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0049] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A barium titanate-based ceramic, characterized in that, The chemical formula is shown below: 0.48(Ba 0.76 Ca 0.2 Sr 0.04 TiO3)-(0.52-x)Bi(Mg 0.5 Ti 0.5 )O3-x(0.88NaNbO3-0.12CaTiO3); where, 0 <x<0.2。 2. The barium titanate-based ceramic according to claim 1, characterized in that, The value of x is between 0.1 and 0.
18.
3. The barium titanate-based ceramic according to claim 1 or 2, characterized in that, Within the temperature range of -70℃ to 300℃, the relative permittivity of the barium titanate-based ceramic is ≥600.
4. The barium titanate-based ceramic according to claim 1 or 2, characterized in that, Within the temperature range of -70℃ to 300℃, the total capacitance deviation of the barium titanate-based ceramic is <10%.
5. A method for preparing barium titanate-based ceramics according to any one of claims 1-4, characterized in that, Includes the following steps: Weigh each metal source according to the stoichiometric ratio shown in the chemical formula of barium titanate-based ceramic, add grinding aid and perform first ball milling to obtain the first mixture; The first mixture is dried and then subjected to a first sintering to obtain a second mixture; Add a sintering aid and a grinding aid to the second mixture and perform a second ball milling to obtain a third mixture; After the third mixture is dried, a binder is added, and the mixture is pressed and sintered in the second stage to obtain a green embryo. The green body is subjected to a third sintering to obtain the barium titanate-based ceramic.
6. The method for preparing barium titanate-based ceramics according to claim 5, characterized in that, The metal source includes metal oxides and metal carbonates, and the grinding aid includes ethanol.
7. The method for preparing barium titanate-based ceramics according to claim 5, characterized in that, The working conditions for the first sintering include: a temperature of 800℃-900℃ and a time of 2.5h-4h.
8. The method for preparing barium titanate-based ceramics according to claim 5, characterized in that, The working conditions for the second sintering include: a temperature of 550℃-650℃ and a time of 2.5h-4h. The binder includes polyvinyl alcohol, the sintering aid includes MnO2, and the working conditions for the compression molding include: pressure of 150MPa-250MPa and time of 5min-15min.
9. The method for preparing barium titanate-based ceramics according to claim 5, characterized in that, The working conditions for the third sintering process include: a temperature of 1050℃-1200℃ and a time of 1.5h-4h.
10. An energy storage device, characterized in that, This includes barium titanate-based ceramics as described in any one of claims 1-4, or barium titanate-based ceramics prepared by the method described in any one of claims 5-9.